Catalyst for dehydrogenating ethylbenzene to produce styrene, preparation method and application thereof
By adding iron niobate and CoO or NiO to the ethylbenzene dehydrogenation catalytic system of iron-potassium-cerium-tungsten-bellium-strontium, a low-potassium catalyst suitable for high pressure and low water ratio was prepared, which solved the problem of low activity and poor stability of the catalyst under this condition, and achieved efficient styrene production.
Patent Information
- Application Number
- CN202111136607.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-27
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-09-27
AI Technical Summary
The existing low-potassium catalysts have low activity and poor stability under high pressure and low water ratio conditions, and potassium is easily lost during the catalytic dehydrogenation reaction, resulting in catalyst deactivation.
A catalyst with low potassium content but high activity and stability under high pressure and low water ratio conditions were prepared by adding iron niobate to an ethylbenzene dehydrogenation catalytic system of iron-potassium-cerium-tungsten-beryllium-strontium.
It significantly enhances the anti-reduction property of the catalyst, delays the potassium loss rate, and improves the stability and activity of the catalyst. The conversion rate of ethylbenzene can reach 74.8%, and the conversion rate of 72.9% can be maintained after a stable operation of 1,600 hours, and the catalyst deactivation rate is only 0.32%/h.
Smart Images

Figure BDA0003282606950000041 
Figure BDA0003282606950000042 
Figure BDA0003282606950000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dehydrogenation catalysts, and in particular to a high-pressure resistant low-water ratio ethylbenzene dehydrogenation catalyst for preparing styrene, and a preparation method and application thereof. Background Art
[0002] The main reaction of ethylbenzene dehydrogenation is C6H5-C2H5→C6H5CH=CH2+H2+124KJ / mol. From a thermodynamic point of view, reducing the partial pressure of ethylbenzene is beneficial to the equilibrium, so water vapor is usually added in industry to promote the reaction to move toward the product. The latest development trend of ethylbenzene dehydrogenation technology to produce styrene is to reduce raw material consumption and improve energy efficiency. The latent heat of vaporization of water is very large. The styrene production process consumes a large amount of superheated steam as a dehydrogenation medium, which makes the process energy-intensive and the production cost high. The development of low-water ratio catalysts suitable for isothermal fixed beds with a water ratio (ratio of water vapor to ethylbenzene) lower than 1.0 (weight) and the subsequent reduction of the operating water ratio of industrial units has become an urgent need for styrene units, especially large-scale styrene units. At present, many styrene units at home and abroad have been in operation for more than 20 years, and the pressure conditions are poor. It is urgent to develop catalysts suitable for high pressure and low water ratio conditions.
[0003] Industrially, ethylbenzene dehydrogenation to produce styrene generally uses an iron-based catalyst with iron oxide as the main active component and potassium oxide as the main co-catalyst. The potassium content is usually greater than 15%. Potassium will be lost in small amounts under the flushing of high-temperature steam and ethylbenzene raw materials. The lost potassium exists in the oil phase of the dehydrogenation liquid in the form of metal ions, which is an important cause of catalyst deactivation. Therefore, achieving a potassium content of less than 10% is the research and development focus of ethylbenzene dehydrogenation catalysts. However, when low-potassium catalysts operate under high pressure and low water ratio conditions, the active phase KFeO2 and the potassium storage phase KFe 11 O 17 It is easy to be reduced and has poor stability, so it is crucial to enhance the reduction resistance of low-potassium catalysts.
[0004] European patent EP0177832 discloses that after adding 1.8-5.4% (by weight) beryllium oxide to the catalyst, it exhibits good stability at a water ratio of less than 2.0 (by weight), but the potassium content of the catalyst is relatively high, greater than 20%. CN95111761.0 discloses that adding multiple metal oxides and silica sol to the Fe-K-Cr system, the catalyst prepared is suitable for operation at a low water ratio, but the catalyst contains Cr, which pollutes the environment and has been eliminated.
[0005] As the scale of styrene plants increases, energy conservation becomes increasingly important. Therefore, developing a low-potassium catalyst suitable for operation under high pressure and low water ratio conditions is an important research direction. Summary of the invention
[0006] One of the technical problems to be solved by the present invention is that the low potassium catalyst in the prior art has low activity and poor stability under high pressure and low water ratio conditions, and a new catalyst for dehydrogenating ethylbenzene to prepare styrene is provided. The catalyst has the characteristics of low potassium content, high reaction activity and good stability for dehydrogenating ethylbenzene to prepare styrene under high pressure and low water ratio conditions.
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing a catalyst for dehydrogenating ethylbenzene to produce styrene corresponding to the first technical problem to be solved.
[0008] The third technical problem to be solved by the present invention is to provide a method for preparing styrene by dehydrogenating ethylbenzene corresponding to the first technical problem to be solved.
[0009] In order to solve one of the above technical problems, the technical solution adopted by the present invention is as follows:
[0010] A catalyst for preparing styrene by dehydrogenating ethylbenzene, comprising the following components based on the mass of the catalyst:
[0011] (a) 67% to 74% Fe2O3;
[0012] (b) 2.5% to 10.5% FeNb2O6;
[0013] (c) 4% to 9% K2O;
[0014] (d) 5.5% to 9% CeO2;
[0015] (e) 0.5% to 5% WO3;
[0016] (f) 0.5% to 5% BeO;
[0017] (g) 0.5% to 5% SrO;
[0018] (h) 0.5% to 5% of at least one selected from CoO and NiO.
[0019] In the above technical solution, the FeNb2O6 content in the catalyst is preferably 3% to 9%.
[0020] In the above technical solution, in the catalyst, Ce is not introduced into the catalyst in the form of cerium oxide, but preferably, is introduced into the catalyst in the form of cerium acetate and / or cerium oxalate.
[0021] In the above technical solution, the content of CoO and / or NiO in the catalyst is preferably 1% to 4%.
[0022] In the above technical solution, it is preferred to include CoO and NiO at the same time. The two oxides have a binary synergistic effect on improving the catalyst activity under high pressure and low water ratio, wherein the usage ratio of CoO and NiO is not particularly limited.
[0023] In the above technical solution, the catalyst does not contain molybdenum oxide.
[0024] In the above technical solution, the catalyst does not contain a binder component.
[0025] In the above technical solution, the catalyst also contains ZrO2, and the content of ZrO2 is 0.1% to 5% based on the mass of the catalyst.
[0026] To solve the second of the above technical problems, the technical solution adopted by the present invention is as follows:
[0027] The method for preparing the catalyst in the technical solution of one of the above technical problems comprises the following steps:
[0028] The catalyst is obtained by mixing Fe source, K source, FeNb2O6, Ce source, W source, Be source, Sr source, Co source and / or Ni source, porogen and water, and then drying and calcining.
[0029] In the above technical solution, preferably, Fe source, K source, Ce source, W source, Be source, Sr source, Co source and / or Ni source are mixed with a porogen, and then FeNb2O6 is added and mixed continuously, and then water (preferably deionized water) is added and mixed to form a catalyst intermediate; and then the catalyst intermediate is dried and calcined to obtain the catalyst. The purpose of the mixing is to achieve particle refinement and uniform mixing.
[0030] In the above technical solution, the Fe source is yellow iron oxide. The K source is potassium carbonate. The Ce source is cerium oxalate and / or cerium acetate. The W source is at least one of tungsten salts or tungsten oxides. The Be source is at least one of Be oxides, hydroxides or beryllium salts. The Sr source is at least one of Sr oxides, hydroxides or strontium salts. The Co source is cobalt oxide. The Ni source is nickel oxide.
[0031] In the above technical solution, the porogen is selected from at least one of graphite, polystyrene microspheres or sodium carboxymethyl cellulose, preferably graphite. The amount of the porogen added is 3.8% to 6.7% based on the weight of the catalyst.
[0032] In the above technical solution, no binder is added during the catalyst preparation process, and the binder includes at least one of kaolin, diatomaceous earth and cement.
[0033] In the above technical solution, there is no particular restriction on the amount of deionized water added. Those skilled in the art can reasonably control the dryness and wetness for extrusion needs, for example but not limited to the amount of water added accounting for 21.7% to 35.9% of the total weight of the catalyst raw material.
[0034] In the above technical solution, in the catalyst preparation method, the drying adopts a two-step method, namely, drying at 35-85°C for 0.5-4 hours and drying at 105-135°C for 0.5-4 hours.
[0035] In the above technical scheme, in the catalyst preparation method, the calcination adopts a four-step method, namely calcination at 350-450°C for 0.5-2 hours, calcination at 500-600°C for 1-4 hours, calcination at 650-750°C for 1-4 hours, and calcination at 800-900°C for 1-4 hours.
[0036] To solve the third of the above technical problems, the technical solution of the present invention is as follows:
[0037] A method for preparing styrene by dehydrogenating ethylbenzene in the presence of the catalyst in the technical solution of one of the above technical problems.
[0038] In the above technical scheme, the operating conditions for ethylbenzene dehydrogenation include: reaction temperature of 580-630°C, liquid volume space velocity of 0.4-0.7 hours -1 , water ratio (weight) is 0.65~0.85, and pressure is -10~30kPa.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] After extensive research, the inventors found that the present invention can significantly enhance the activity and stability of low-potassium catalysts under high pressure and low water ratio conditions by adding ferric niobate and at least one selected from CoO or NiO to the iron-potassium-cerium-tungsten-beryllium-strontium ethylbenzene dehydrogenation catalytic system. The possible reason is that it can effectively improve the anti-reduction property of the catalyst active phase KFeO2, greatly slowing down the loss rate of potassium during the catalytic dehydrogenation reaction of ethylbenzene. On the other hand, without the introduction of a binder component, the active phase of the catalyst is further stabilized and dispersed, accelerating the rate of water vapor and carbon deposited on the catalyst surface to produce water gas reaction. The activity and stability of the catalyst of the present invention were evaluated in an isothermal fixed bed. At 15kPa and a liquid volume space velocity of 0.5h / min, the catalyst was stable and stable. -1 , 620℃, water ratio from the usual 2.0 (weight) to 0.7 (weight) conditions, ethylbenzene conversion can reach 74.8%, after 1600 hours of stable operation ethylbenzene conversion can still be as high as 72.9%, the catalyst deactivation rate can be only 0.32% / h, the dehydrogenation liquid oil phase K + The concentration can be as low as 0.0001 mg / L, achieving good technical results. DETAILED DESCRIPTION
[0041] The present invention will be further described in detail below by way of examples.
[0042] In the examples of the present invention and the comparative examples, the activity of the catalyst was evaluated in an isothermal fixed bed. For the activity evaluation of the catalyst for dehydrogenation of ethylbenzene to produce styrene, the process is briefly described as follows:
[0043] Deionized water and ethylbenzene are respectively fed into the preheating mixer through metering pumps, and then preheated and mixed into gaseous state before entering the reactor, which is heated by electric heating wire to reach a predetermined temperature. The reactor is a stainless steel tube with an inner diameter of 1″, filled with 100 ml of catalyst with a particle size of 3 mm. The reactants flowing out of the reactor are condensed with water and analyzed for their composition by gas chromatography.
[0044] The ethylbenzene conversion rate and styrene selectivity are calculated according to the following formula:
[0045]
[0046]
[0047] The catalyst stability of the present invention is expressed by the catalyst deactivation rate, which is calculated as follows:
[0048] Catalyst deactivation rate = [(reaction initial conversion rate - reaction final conversion rate) / reaction time h] × 100%,
[0049] The greater the catalyst deactivation rate, the worse the catalyst stability; the smaller the catalyst deactivation rate, the better the catalyst stability.
[0050] The loss of active components in the catalyst sample of the present invention is a measure of the K + The concentration was measured using a PE-Zeeman 5000 atomic absorption spectrometer with an analytical line of 404.4 nm, a lamp current of 10 mA, and a slit of 0.7 nm.
[0051] [Example 1]
[0052] Yellow iron oxide equivalent to 72.09 parts of Fe2O3, potassium carbonate equivalent to 6.16 parts of K2O, cerium acetate equivalent to 6.83 parts of CeO2, ammonium tungstate equivalent to 2.41 parts of WO3, beryllium hydroxide equivalent to 1.21 parts of BeO, 2.78 parts of SrO, 3.84 parts of CoO and 4.96 parts of graphite were stirred in a kneader for 0.3 hours, 4.68 parts of FeNb2O6 were added, and the mixture was stirred for another 1.7 hours. Deionized water accounting for 25.9% of the total weight of the catalyst raw material was added, stirred for 0.5 hour, the extruded strips were taken out, extruded into particles with a diameter of 3 mm and a length of 6 mm, placed in an oven, baked at 58°C for 2.5 hours, and baked at 128°C for 3 hours, and then placed in a muffle furnace, calcined at 375°C for 0.75 hour, 525°C for 2.5 hours, 715°C for 2.5 hours, and 885°C for 2.5 hours to obtain a finished catalyst. The catalyst composition is listed in Table 1.
[0053] 100 ml of catalyst was loaded into the reactor and heated at 15 kPa and a liquid volume space velocity of 0.5 h. -1 The activity and stability were evaluated under the conditions of 620°C and water ratio (weight) of 0.7. The catalyst deactivation rate was 0.5% / h. The evaluation results are listed in Table 2. When the evaluation was performed for 1600 hours, the dehydrogenated liquid was collected, and the aqueous phase and the oil phase were separated. + The concentrations were measured and the results are listed in Table 2.
[0054] [Comparative Example 1]
[0055] Except for the absence of FeNb2O6 and CoO, the catalyst preparation method, catalyst evaluation conditions and K + The concentration analysis method is the same as that in Example 1. The specific composition is: yellow iron oxide equivalent to 72.09 parts of Fe2O3, potassium carbonate equivalent to 6.16 parts of K2O, cerium acetate equivalent to 6.83 parts of CeO2, ammonium tungstate equivalent to 2.41 parts of WO3, beryllium hydroxide equivalent to 1.21 parts of BeO, 2.78 parts of SrO and 4.54 parts of graphite. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0056] [Comparative Example 2]
[0057] Except for using Fe2O3 and Nb2O5 to replace the same proportion of FeNb2O6, the catalyst preparation method, catalyst evaluation conditions and K +The concentration analysis method is the same as that in Example 1. The specific composition is: yellow iron oxide equivalent to 73.2 parts of Fe2O3, potassium carbonate equivalent to 6.16 parts of K2O, cerium acetate equivalent to 6.83 parts of CeO2, ammonium tungstate equivalent to 2.41 parts of WO3, beryllium hydroxide equivalent to 1.21 parts of BeO, 2.78 parts of SrO, 3.84 parts of CoO, 3.57 parts of Nb2O5 and 4.96 parts of graphite. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0058] [Example 2]
[0059] The catalyst was prepared and tested according to the method of Example 1, except that NiO was used instead of CoO.
[0060] The composition of the catalyst is shown in Table 1. The evaluation results and K + The concentration analysis results are listed in Table 2.
[0061] [Comparative Example 3]
[0062] Except for using Fe2O3 and Nb2O5 to replace the same proportion of FeNb2O6, the catalyst preparation method, catalyst evaluation conditions and K + The concentration analysis method is the same as that in Example 2. The specific composition is: yellow iron oxide equivalent to 73.2 parts of Fe2O3, potassium carbonate equivalent to 6.16 parts of K2O, cerium acetate equivalent to 6.83 parts of CeO2, ammonium tungstate equivalent to 2.41 parts of WO3, beryllium hydroxide equivalent to 1.21 parts of BeO, 2.78 parts of SrO, 3.84 parts of NiO, 3.57 parts of Nb2O5 and 4.96 parts of graphite. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0063] [Example 3]
[0064] The catalyst was prepared and tested as in Example 1, except that 2.04 parts of CoO and 1.8 parts of NiO were used in place of 3.84 parts of CoO.
[0065] The composition of the catalyst is shown in Table 1. The evaluation results and K + The concentration analysis results are listed in Table 2.
[0066] [Example 4]
[0067] The catalyst was prepared and tested according to the method of Example 1. The specific composition was: yellow iron oxide equivalent to 67.16 parts of Fe2O3, 8.86 parts of FeNb2O6, 5.24 parts of potassium carbonate equivalent to K2O, 8.95 parts of cerium acetate equivalent to CeO2, 0.58 parts of ammonium tungstate equivalent to WO3, 0.61 parts of beryllium hydroxide equivalent to BeO, 4.24 parts of strontium carbonate equivalent to SrO, 3.84 parts of CoO, 0.52 parts of ZrO2 and 4.96 parts of graphite. The catalyst composition is listed in Table 1, and the evaluation results and the analysis results of K+ concentration in the dehydrogenated liquid oil phase are listed in Table 2.
[0068] [Example 5]
[0069] The catalyst was prepared and tested according to the method of Example 1. The specific composition was: yellow iron oxide equivalent to 69.36 parts of Fe2O3, 10.15 parts of FeNb2O6, 5.42 parts of potassium carbonate equivalent to 5.98 parts of CeO2, 0.58 parts of ammonium tungstate equivalent to 0.61 parts of BeO, 4.24 parts of SrO2 equivalent to strontium carbonate, 3.66 parts of CoO and 4.96 parts of graphite. The catalyst composition is listed in Table 1. The evaluation results and the K content in the dehydrogenated liquid oil phase are shown in Table 1. + The concentration analysis results are listed in Table 2.
[0070] [Example 6]
[0071] The catalyst was prepared and tested according to the method of Example 1. The specific composition was: yellow iron oxide equivalent to 71.79 parts of Fe2O3, 2.79 parts of FeNb2O6, 8.92 parts of potassium carbonate equivalent to 8.92 parts of K2O, 7.05 parts of cerium acetate equivalent to 7.05 parts of CeO2, 4.6 parts of ammonium tungstate equivalent to 4.6 parts of WO3, 1.38 parts of beryllium hydroxide equivalent to BeO, 0.95 parts of SrO, 2.52 parts of CoO and 4.96 parts of graphite. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0072] [Example 7]
[0073] The catalyst was prepared and tested according to the method of Example 1. The specific composition was: yellow iron oxide equivalent to 70.12 parts of Fe2O3, 5.15 parts of FeNb2O6, 5.35 parts of potassium carbonate equivalent to 5.13 parts of CeO2, 3.1 parts of ammonium tungstate equivalent to 3.1 parts of WO3, 3.76 parts of beryllium hydroxide equivalent to BeO, 2.47 parts of strontium carbonate equivalent to SrO, 4.92 parts of CoO and 4.96 parts of graphite. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0074] [Example 8]
[0075] The catalyst was prepared and tested according to the method of Example 1. The specific composition was: yellow iron oxide equivalent to 73.21 parts of Fe2O3, 3.45 parts of FeNb2O6, 4.32 parts of potassium carbonate equivalent to K2O, 8.15 parts of cerium acetate equivalent to CeO2, 3.86 parts of ammonium tungstate equivalent to WO3, 4.76 parts of beryllium hydroxide equivalent to BeO, 1.47 parts of SrO, 0.78 parts of CoO and 4.96 parts of graphite. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0076] [Comparative Example 4]
[0077] The catalyst was prepared and tested as in Example 8, except that 73.21 parts of Fe2O3 yellow iron oxide was replaced with 53.88 parts of Fe2O3 red iron oxide and 19.33 parts of Fe2O3 yellow iron oxide.
[0078] The composition of the catalyst is shown in Table 1. The evaluation results and K + The concentration analysis results are listed in Table 2.
[0079] [Comparative Example 5]
[0080] The catalyst was prepared and tested as in Example 8, except that cerium oxide was used instead of cerium acetate.
[0081] The composition of the catalyst is shown in Table 1. The evaluation results and K + The concentration analysis results are listed in Table 2.
[0082] [Comparative Example 6]
[0083] The catalyst was tested according to the method of Example 1. The preparation method and specific composition were as follows: yellow iron oxide equivalent to 72.09 parts of Fe2O3, 4.68 parts of FeNb2O6, potassium carbonate equivalent to 6.16 parts of K2O, cerium acetate equivalent to 6.83 parts of CeO2, ammonium tungstate equivalent to 2.41 parts of WO3, beryllium hydroxide equivalent to 1.21 parts of BeO, 2.78 parts of SrO, 3.84 parts of CoO and 4.96 parts of graphite were stirred in a kneader for 2.0 hours. , add deionized water accounting for 25.9% of the total weight of the catalyst raw material, stir for 0.5 hour, take out the extruded strips, extrude into particles with a diameter of 3 mm and a length of 6 mm, put them into an oven, bake them at 58°C for 2.5 hours, bake them at 128°C for 3 hours, then place them in a muffle furnace, roast them at 375°C for 0.75 hour, roast them at 525°C for 2.5 hours, roast them at 715°C for 2.5 hours, and roast them at 885°C for 2.5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1. The evaluation results and K content in the dehydrogenated liquid oil phase are shown in Table 1. + The concentration analysis results are listed in Table 2.
[0084] [Comparative Example 7]
[0085] The catalyst was prepared and tested according to the method of Example 1. The specific composition was: yellow iron oxide equivalent to 71.01 parts of Fe2O3, 4.58 parts of FeNb2O6, 6.39 parts of potassium carbonate equivalent to 6.93 parts of CeO2, 2.41 parts of ammonium tungstate equivalent to WO3, 1.21 parts of beryllium hydroxide equivalent to BeO, 2.78 parts of SrO, 3.84 parts of CoO, 0.85 parts of cement and 4.96 parts of graphite. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0086] [Comparative Example 8]
[0087] The catalyst was prepared and tested according to the method of Example 1, except that ammonium molybdate was used instead of ammonium tungstate.
[0088] The composition of the catalyst is shown in Table 1. The evaluation results and K + The concentration analysis results are listed in Table 2.
[0089] [Comparative Example 9]
[0090] The catalyst and the test catalyst were prepared according to the method of Example 1, and the specific composition was: yellow iron oxide equivalent to 68.55 parts of Fe2O3, potassium carbonate equivalent to 4.76 parts of K2O, cerium acetate equivalent to 5.2 parts of CeO2, ammonium tungstate equivalent to 2.41 parts of WO3, beryllium hydroxide equivalent to 1.21 parts of BeO, strontium carbonate equivalent to 2.78 parts of SrO, 3.84 parts of CoO and 4.96 parts of graphite, stirred in a kneader for 0.3 hours, and 11.25 parts of FeNb2O6 were added. , and then stirred for 1.7 hours, added deionized water accounting for 25.9% of the total weight of the catalyst raw material, stirred for 0.5 hours, took out the extruded strips, extruded into particles with a diameter of 3 mm and a length of 6 mm, put them into an oven, baked at 58°C for 2.5 hours, and baked at 128°C for 3 hours, and then placed in a muffle furnace, calcined at 375°C for 0.75 hours, 525°C for 2.5 hours, 715°C for 2.5 hours, and 885°C for 2.5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0091] [Comparative Example 10]
[0092] The catalyst and the test catalyst were prepared according to the method of Example 1. The specific composition was: yellow iron oxide equivalent to 72.58 parts of Fe2O3, potassium carbonate equivalent to 4.33 parts of K2O, cerium acetate equivalent to 6.17 parts of CeO2, ammonium tungstate equivalent to 2.41 parts of WO3, beryllium hydroxide equivalent to 1.21 parts of BeO, 2.78 parts of SrO, 5.84 parts of CoO and 4.96 parts of graphite. The mixture was stirred in a kneader for 0.3 hour, 4.68 parts of FeNb2O6 were added, and the mixture was stirred for 1 hour. The mixture was stirred for 1.7 hours, deionized water accounting for 25.9% of the total weight of the catalyst raw material was added, stirred for 0.5 hours, the extruded strips were taken out, extruded into particles with a diameter of 3 mm and a length of 6 mm, placed in an oven, and baked at 58°C for 2.5 hours, 128°C for 3 hours, and then placed in a muffle furnace and calcined at 375°C for 0.75 hour, 525°C for 2.5 hours, 715°C for 2.5 hours, and 885°C for 2.5 hours to obtain a finished catalyst. The catalyst composition is listed in Table 1. The evaluation results and K content in the dehydrogenated liquid oil phase are shown in Table 1. + The concentration analysis results are listed in Table 2.
[0093] [Comparative Example 11]
[0094] The catalyst and the test catalyst were prepared according to the method of Example 1, and the specific composition was: yellow iron oxide equivalent to 73.88 parts of Fe2O3, potassium carbonate equivalent to 6.33 parts of K2O, cerium acetate equivalent to 6.17 parts of CeO2, ammonium tungstate equivalent to 2.41 parts of WO3, beryllium hydroxide equivalent to 1.21 parts of BeO, strontium carbonate equivalent to 2.78 parts of SrO and 4.96 parts of graphite, which were stirred in a kneader for 0.3 hours, 7.22 parts of FeNb2O6, and then stirred for 1 hour. .7 hours, add deionized water accounting for 25.9% of the total weight of the catalyst raw material, stir for 0.5 hours, take out the extruded strips, extrude into particles with a diameter of 3 mm and a length of 6 mm, put them into an oven, bake at 58°C for 2.5 hours, bake at 128°C for 3 hours, then place them in a muffle furnace, roast at 375°C for 0.75 hours, roast at 525°C for 2.5 hours, roast at 715°C for 2.5 hours, and roast at 885°C for 2.5 hours to obtain the finished catalyst. The catalyst composition is listed in Table 1. The evaluation results and K in the dehydrogenated liquid oil phase + The concentration analysis results are listed in Table 2.
[0095] Table 1 Weight percentage composition of catalyst (to be continued)
[0096]
[0097] Table 1 Weight percent composition of catalyst (continued)
[0098] Composition content Example 8 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Comparative Example 11 <![CDATA[Fe2O3]]> 73.21 73.21 73.21 72.09 71.01 72.09 68.55 72.58 73.88 <![CDATA[FeNb2O6]]> 3.45 3.45 3.45 4.68 4.58 4.68 11.25 4.68 7.22 <![CDATA[K2O]]> 4.32 4.32 4.32 6.16 6.39 6.16 4.76 4.33 6.33 <![CDATA[CeO2]]> 8.15 8.15 8.15 6.83 6.93 6.83 5.2 6.17 6.17 <![CDATA[WO3]]> 3.86 3.86 3.86 2.41 2.41 0 2.41 2.41 2.41 BeO 4.76 4.76 4.76 1.21 1.21 1.21 1.21 1.21 1.21 SrO 1.47 1.47 1.47 2.78 2.78 2.78 2.78 2.78 2.78 CoO 0.78 0.78 0.78 3.84 3.84 3.84 3.84 5.84 0 cement 0 0 0 0 0.85 0 0 0 0 <![CDATA[MoO3]]> 0 0 0 0 0 2.41 0 0 0
[0099] Table 2 Comparison of catalyst performance
[0100]
[0101] The embodiments of the present invention are only detailed descriptions of the technical solutions of the present invention, but the present invention is not limited to the above embodiments, that is, the present invention can be implemented without relying on the steps described in the above embodiments. In summary, any improvements made by those skilled in the art to the present invention, including replacement of the raw materials and additives described in the present invention, selection of specific implementation methods, etc., all belong to the protection scope and disclosure scope of the present invention.
Claims
1. A catalyst for dehydrogenating ethylbenzene to produce styrene, comprising the following components, based on the mass of the catalyst: (a) 67% to 74% Fe2O3; (b) 2.5% to 10.5% FeNb2O6; (c) 4% to 9% K2O; (d) 5.5% to 9% CeO2; (e) 0.5% to 5% WO3; (f) 0.5% to 5% BeO; (g) 0.5% to 5% SrO; (h) 0.5% to 5% of at least one selected from CoO and NiO; Ce is introduced into the catalyst in the form of cerium acetate and / or cerium oxalate; and the catalyst does not contain a binder.
2. The catalyst according to claim 1, characterized in that In the catalyst, the content of FeNb2O6 is 3% to 9%; and / or the content of CoO and / or NiO is 1% to 4%.
3. The catalyst according to claim 1, characterized in that The catalyst does not contain molybdenum oxide.
4. The catalyst according to any one of claims 1 to 3, characterized in that The catalyst also contains ZrO2, and the content of ZrO2 is 0.1% to 5% based on the mass of the catalyst.
5. A method for preparing a catalyst according to any one of claims 1 to 3, comprising the following steps: The catalyst is obtained by mixing Fe source, K source, FeNb2O6, Ce source, W source, Be source, Sr source, Co source and / or Ni source, porogen and water, and then drying and calcining.
6. The preparation method according to claim 5, characterized in that: The Fe source, K source, Ce source, W source, Be source, Sr source, Co source and / or Ni source are mixed with the porogen, and then FeNb2O6 is added and continued to be mixed, and then water is added to mix and shape, and the catalyst is obtained after drying and calcination.
7. The preparation method according to claim 5 or 6, characterized in that: The Fe source is yellow iron oxide; the K source is potassium carbonate; the Ce source is cerium oxalate and / or cerium acetate; the W source is at least one of tungsten salts or tungsten oxides; the Be source is at least one of Be oxides, hydroxides or beryllium salts; the Sr source is at least one of Sr oxides, hydroxides or strontium salts; the Co source is cobalt oxide; and the Ni source is nickel oxide.
8. The preparation method according to claim 5 or 6, characterized in that: No binder is added during the preparation of the catalyst.
9. The preparation method according to claim 5 or 6, characterized in that: The drying adopts a two-step method, namely, drying at 35-85° C. for 0.5-4 hours and drying at 105-135° C. for 0.5-4 hours.
10. The preparation method according to claim 5 or 6, characterized in that: The calcination adopts a four-step method, namely, calcination at 350-450°C for 0.5-2 hours, calcination at 500-600°C for 1-4 hours, calcination at 650-750°C for 1-4 hours, and calcination at 800-900°C for 1-4 hours.
11. Use of the catalyst according to any one of claims 1 to 4 or the catalyst prepared by the preparation method according to any one of claims 5 to 10 in the dehydrogenation of ethylbenzene to produce styrene.
12. The use according to claim 11, characterized in that The operating conditions for the dehydrogenation of ethylbenzene to produce styrene include: reaction temperature of 580-630°C, liquid volume space velocity of 0.4-0.7 hour -1 , the water ratio is 0.65 to 0.85 by weight, and the pressure is -10 to 30 kPa.
Citation Information
Patent Citations
Dehydrogenation catalyst for prodn. of alkylalkenyl aromatic hydrocarbon
CN1145277A
Dehydrogenation catalysts
EP0177832A2
High-strength low-water ratio ethylbenzene dehydrogenation catalyst not containing adhesive
CN106994353A
Dehydrogenation catalyst for preparing styrene and preparation method of catalyst
CN109569639A